Balaton Lake (virtual) projected and perceived destination image amid Covid-19 pandemic. (July 2023) - Dimitrovski, Darko; Sulyok, Judit; Papp, Zsofia
In days gone by, Balaton Lake predominately attracted domestic tourists, without focusing on the countries which neighbour Hungary and their respective markets. However, as a consequence of the Covid-19 pandemic, domestic and regional tourism flows have been stimulated, as travel restrictions resulted in a tendency towards travel to local and neighbouring destinations. In line with these trends, the research investigates the congruence of both Balaton Lake's projected and perceived (virtual) destination image in the era of Covid-19, with Serbia being considered as a neighbouring and emitting market. The study deployed a sequential exploratory mixed-method approach (qualitative and then quantitative). The study contributes to the existing knowledge by addressing the gap between the visual and textual content of a projected (virtual) destination image and by acknowledging non-visitor perception of destination image in the context of pronounced regional international travel.